2012
DOI: 10.1108/17506221211281975
|View full text |Cite
|
Sign up to set email alerts
|

How to reform the power sector in Mexico? Insights from a simulation model

Abstract: PurposeThe purpose of this paper is to address the question of how a developing country, like Mexico, can reform its electricity industry at the same time as addressing climate change issues.Design/methodology/approachThe objective is to provide a tool that policy makers could use to make better and more informed decisions if they decide to liberalise the power sector in Mexico. The problems they would face are difficult to address in an analytically tractable way using conventional economic models. Also, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Emergency service [111] Supply-demand equation that delivers frontline policing services Air transportation [112] policies and strategies for air transportation (e.g., policies for reducing emissions of commercial aviation Local public policy [113] local public policy process Public sector unit [114] mortality rate of public sector units Concession pricing model [115] determining a rational concession price for highway projects based on pro forma financial statements Highway sustainability [116] highway sustainability based on individual policies with a crucial impact on the success of policymaking Academic performance [117] factors that affect academic performance of migrant student residing in poor migrant neighborhoods Maritime Sustainability [118] integrated sustainability assessment process Information in health care [119] emergent market behaviour enabling evaluation of different public health policies Climate change [120] electricity industry at the same time as addressing climate change issues Participatory urban [121] urban sensing for improving municipality's availability of environmental information at comparable cost level Wireless local area [122] effect of subsidization, revenue sharing, and alliance strategies Airport competitiveness [123] airport investment and city R&D inputs, which support decision-makers on airport competitiveness Electronic health records [124] combination of measures can promote the adoption of electronic health records by different stakeholders…”
Section: Topics and Goods Models And Issues Dealtmentioning
confidence: 99%
See 1 more Smart Citation
“…Emergency service [111] Supply-demand equation that delivers frontline policing services Air transportation [112] policies and strategies for air transportation (e.g., policies for reducing emissions of commercial aviation Local public policy [113] local public policy process Public sector unit [114] mortality rate of public sector units Concession pricing model [115] determining a rational concession price for highway projects based on pro forma financial statements Highway sustainability [116] highway sustainability based on individual policies with a crucial impact on the success of policymaking Academic performance [117] factors that affect academic performance of migrant student residing in poor migrant neighborhoods Maritime Sustainability [118] integrated sustainability assessment process Information in health care [119] emergent market behaviour enabling evaluation of different public health policies Climate change [120] electricity industry at the same time as addressing climate change issues Participatory urban [121] urban sensing for improving municipality's availability of environmental information at comparable cost level Wireless local area [122] effect of subsidization, revenue sharing, and alliance strategies Airport competitiveness [123] airport investment and city R&D inputs, which support decision-makers on airport competitiveness Electronic health records [124] combination of measures can promote the adoption of electronic health records by different stakeholders…”
Section: Topics and Goods Models And Issues Dealtmentioning
confidence: 99%
“…Natural-societal risk [106] stratospheric ozone to identify points to influence policymakers in addressing risks in a natural system Waste management [107] cost-benefit of construction and demolition waste management practices Strategic conversations [108] soft operational research strategy making an intervention with a top management team Interactive knowledge management [109] knowledge management for improving quality of knowledge in non-hierarchical policy-making groups Waste management [110] economic feasibility of recycling and ratio of savings to costs in construction and demolition waste management Emergency service [111] Supply-demand equation that delivers frontline policing services Air transportation [112] policies and strategies for air transportation (e.g., policies for reducing emissions of commercial aviation Local public policy [113] local public policy process Public sector unit [114] mortality rate of public sector units Concession pricing model [115] determining a rational concession price for highway projects based on pro forma financial statements Highway sustainability [116] highway sustainability based on individual policies with a crucial impact on the success of policymaking Academic performance [117] factors that affect academic performance of migrant student residing in poor migrant neighborhoods Maritime Sustainability [118] integrated sustainability assessment process Information in health care [119] emergent market behaviour enabling evaluation of different public health policies Climate change [120] electricity industry at the same time as addressing climate change issues Participatory urban [121] urban sensing for improving municipality's availability of environmental information at comparable cost level Wireless local area [122] effect of subsidization, revenue sharing, and alliance strategies Airport competitiveness [123] airport investment and city R&D inputs, which support decision-makers on airport competitiveness Electronic health records [124] combination of measures can promote the adoption of electronic health records by different stakeholders Housing market [125] house prices, balances between supply and demand, construction companies' earnings, and vacancy rates Participatory policy [126] participatory procedures to the governance of wider public policy issues Debt accumulation [127] public debt in developing countries and its two-way linkages with economic growth and public f...…”
Section: Topics and Goods Models And Issues Dealtmentioning
confidence: 99%
“…The model allocated future demand onto five renewable and two fossil-fuel technologies based on the cheapest production cost basis. The same approach of choosing a particular technology has been adopted by Qudrat-Ullah and Davidsen [23] and Fuentes-Bracamontes [25]. Though logical, this approach failed to account for externalities (e.g.…”
Section: Policy Assessment Modelsmentioning
confidence: 99%
“…social and technological advancements) in renewable technologies. In addition, the study assumed capacity replacements prompted by price driven incentives, like Fuentes-Bracamontes [25], which was also not possible as power generation technologies were capital intensive with almost no salvage value. The study showed that emission reduction policy can be successful, if power generation was shifted to renewable resources.…”
Section: Policy Assessment Modelsmentioning
confidence: 99%
See 1 more Smart Citation